The Processes of Memory, Forgetting, and Transfer and Their Implications in the Learning and Learning Process: A Literature Review - Hadi, Harisnal; S, Neviyarni (International Journal of Educational Dynamics, 2022)
The issue of transfer of learning that emerges in the context of education cannot be separated from the problem of remembering and forgetting in learning. Teachers must genuinely anticipate these issues. Each student has unique traits, and they are all unique both physically and psychologically. The goal of this study is to investigate memory, forgetting, and transfer issues in the learning and learning process. It is implied that a teacher shouldn't apply a generalization to all students. A teacher needs to know how to relate to and comprehend his students. However, in practice, teachers have not given this issue their full focus in classrooms. Because teachers play such a crucial role in the entire teaching and learning process, improving the quality of teachers in the teaching and learning process is one of the efforts being made to improve the quality of education. Thus, the topics of memory, forgetting, and learning transfer will be covered in this study.